2008
DOI: 10.1002/aic.11550
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic features of the sonochemical degradation of organic pollutants

Abstract: This work considers the mechanistic features of sonochemical degradation of volatile (chlorobenzene) and nonvolatile (phenol) organic pollutants. The sonochemical degradation of pollutant occurs in two pathways: thermal pyrolysis and hydroxylation. By coupling experimental results to bubble dynamics model, we have tried to establish relative contribution of these pathways to degradation of two kinds of pollutants. It is revealed that degradation of volatile pollutants occurs primarily by thermal pyrolysis whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 79 publications
(102 reference statements)
2
12
0
Order By: Relevance
“…The results of this work confirm this aspect and agree well with similar observations in the literature [21,22]. However, it should be noted that no such systematic studies have been reported in the literature on the degradation of different solvents using hydrodynamic cavitation though some single component studies were reported using conventional cavitating devices such as an orifice.…”
Section: Effect Of Nature Of Solventsupporting
confidence: 92%
See 3 more Smart Citations
“…The results of this work confirm this aspect and agree well with similar observations in the literature [21,22]. However, it should be noted that no such systematic studies have been reported in the literature on the degradation of different solvents using hydrodynamic cavitation though some single component studies were reported using conventional cavitating devices such as an orifice.…”
Section: Effect Of Nature Of Solventsupporting
confidence: 92%
“…This indicates that no side products were formed during the cavitation process. All the FTIR spectra display a very broad absorption in the range 3000-2800 cm 21 with the maximum at 3468, 3450, , which are associated to OAH groups interacting with hydrogen bonds, i.e., molecular water. For toluene, absorbance peaks at 685 and 665 cm 21 corresponds to aromatic CAH out-of-plane bending [36].…”
Section: Mechanism Of Solvent Degradationmentioning
confidence: 99%
See 2 more Smart Citations
“…This model has been extensively described in our previous articles. 33,34 For the convenience of the reader, we reproduce here only the main components of the model and relevant data/boundary conditions. For greater details on this model, we refer the reader to our earlier articles 33,34 as well as the original article of Toegel et al, 32 and Storey and Szeri.…”
Section: Bubble Dynamics Modelmentioning
confidence: 99%